OPTIMIZING THE VALUE CHAIN AND PRODUCT INNOVATION OF NUTMEG (MYRISTICA FRAGRANS) TO EMPOWER FARMERS AND MSMES IN SUKABUMI: OPTIMALISASI RANTAI NILAI DAN INOVASI PRODUK PALA (MYRISTICA FRAGRANS) UNTUK PEMBERDAYAAN PETANI DAN UMKM DI KOTA SUKABUMI - Badrindah Dwanur Pangast; Endang Tri Astutiningsih; Neneng Kartika Rini (ROCE : Jurnal Pertanian Terapan, 2026)
The nutmeg farming sector in Sukabumi City has great economic potential. However, it still faces various obstacles, including low productivity, low farm-level selling prices, and dependence on intermediaries that limit income growth. This study aims to analyze the nutmeg value chain from production by farmers to processing by SMEs and traders, and to assess the value added generated at each stage. The research method is a survey, with primary data collected via questionnaires and interviews with farmers and nutmeg-processing entrepreneurs in Sukabumi. The results indicate an imbalance in the distribution of value added, with processors earning higher margins than farmers. Processed products such as paladang, nutmeg powder, and nutmeg ice cream can generate significant value-added, so developing these products has the potential to improve the welfare of farmers and small businesses. However, limited market access and dependence on intermediaries remain major challenges. Therefore, it is necessary to enhance the capacity of farmers and SMEs through processing technology training, the development of shared processing centers, and the implementation of digital marketing to expand market access and improve supply chain efficiency. Government policy support and collaboration with relevant institutions are also crucial to address issues related to raw material supply, land constraints, and infrastructure, thereby fostering sustainable economic benefits in the nutmeg sector of Sukabumi.